PEMBERDAYAAN GURU DAN SISWA SMK KESEHATAN PGRI DENPASAR MELALUI PELATIHAN FORMULASI SABUN CAIR DAN LITERASI FINANSIAL BERBASIS INVESTASI DIGITAL - Made Dharmesti Wijaya; Anak Agung Gede Indraningrat; Idawati Ida Ayu Agung; Saputri Legis Ocktaviana (Universitas Mataram, 2026)
Improving human resource competencies in the health and economic sectors is essential for supporting high-quality vocational education that can adapt to evolving societal and workforce demands. Teachers and students in vocational health schools are expected not only to master pharmaceutical knowledge and technical skills but also to develop practical competencies and adequate financial literacy. Preliminary discussions revealed that the partners faced challenges related to limited skills in formulating simple and applicable pharmaceutical products, as well as insufficient financial literacy, particularly in financial planning and digital investment. This community service program aimed to enhance the competencies of teachers and students of the Pharmacy Department at SMK Kesehatan PGRI Denpasar in both health and economic aspects. The program was conducted on January 23, 2026, at the Pharmacy Laboratory of SMK Kesehatan PGRI Denpasar and involved 17 participants consisting of pharmacy teachers and twelfth-grade students. The methods employed included a focus group discussion to identify the partners’ priority issues, interactive educational sessions, hands-on formulation training, and evaluation through pretest and posttest assessments. The health-related training focused on the formulation of liquid soap products, including dishwashing liquid and floor cleaner, covering raw materials, formulation procedures, hygiene principles, and product quality considerations. In the economic component, participants received training on digital investment-based financial literacy. Evaluation results demonstrated a substantial improvement in participants’ understanding, as indicated by an increase in the average score from 52.94 to 85.88. Post-program monitoring further showed that the partners had utilized the provided resources and independently replicated the liquid soap formulation process. Therefore, this community service program was effective in improving the knowledge and skills of teachers and students in simple pharmaceutical product formulation and digital investment-based financial literacy.